Nuclear weapons, the United States and alliances in Europe and Asia: Toward an institutional perspective. Issue 1 (2nd January 2017) - Frühling, Stephan; O'Neil, Andrew
ABSTRACT: America's alliances in Europe and East Asia all involve some institutional cooperation on U.S. nuclear weapons policy, planning or employment—from consultative fora in Asia to joint policy and sharing of nuclear warheads in NATO. Such cooperation is often analyzed through the prism of "extended nuclear deterrence, " which focuses on the extension of U.S. security guarantees and their effect on potential adversaries. This article argues that this underplays the importance of institutional factors: Allies have historically addressed a range of objectives through such cooperation, which has helped to catalyze agreements about broader alliance strategy. The varied form such cooperation takes in different alliances also flows from the respective bargaining power of allies and the relative importance of consensus, rather than perceived threats. The article concludes that nuclear weapons cooperation will remain crucial in successful U.S. alliance management, as allies negotiate their relationship with each other in the face of geostrategic change.